ANALYSIS OF COST AND TIME CONTROL ON THE LIBRARY CONSTRUCTION PROJECT OF THE POLICE TRAINING INSTITUTE USING THE EARNED VALUE - Xena S P, Canda; Bangun, Sempurna; Dewita, Hikma; Naibaho, Pio Ranap Tua (International Journal of Civil Engineering and Infrastructure, 2024)
In a construction project, the factors that become indicators of the success of a project are that it must be cost, time and quality that can be achieved by planning, scheduling, and controlling its implementation properly. The method used to analyze data regarding cost control and project implementation time so that it can be effective and efficient is to use the concept of the value of the results (Earned Value Concept). From the data that has been obtained, the next step is to calculate the work weight for each item. Then an analysis of cost and time control is carried out using several approaches, namely: BCWS, BCWP and ACWP. The results of project data processing use the analysis calculation of the result value method. From the calculation of the Schadule Variance (SV) the work accelerates 1 week from the predetermined schedule. the total schedule/schedule 17 weeks of work and the results of the calculation on the 17th week is 2,710,716.28. Showing a positive number, this indicates that the implementation of the work is faster than the planned schedule. From the results of the calculation of Cost Variance (CV) the work has accelerated by 1 week from the predetermined schedule. week 17 is 2,011,321,591.90. Showing a positive number, this indicates that the cost to complete the project is less than the planned cost. The calculation result of the Schedule Performance Index (SPI) that the work has accelerated 1 week from the predetermined schedule. In week 1 to week 17 of 1.00, it shows that the project was carried out on time. The results of the calculation of the Cost Performance Index (CPI) of work accelerated by 1 week from the predetermined schedule. In the 1st week to the 17th week of 1.00 indicates that the work in the field costs in accordance with the planned budget